2022
DOI: 10.3390/cells11142216
|View full text |Cite
|
Sign up to set email alerts
|

BMP Signaling Pathway in Dentin Development and Diseases

Abstract: BMP signaling plays an important role in dentin development. BMPs and antagonists regulate odontoblast differentiation and downstream gene expression via canonical Smad and non-canonical Smad signaling pathways. The interaction of BMPs with their receptors leads to the formation of complexes and the transduction of signals to the canonical Smad signaling pathway (for example, BMP ligands, receptors, and Smads) and the non-canonical Smad signaling pathway (for example, MAPKs, p38, Erk, JNK, and PI3K/Akt) to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 404 publications
0
34
0
1
Order By: Relevance
“…BMP-4 mRNA levels were also increased by CHI–HAp–collagen. BMP-4 is a member of the transforming growth factor superfamily that is important in tooth generation and formation, osteoblast differentiation, and matrix secretion [ 51 ]. On the other hand, the level of RUNX2 mRNA was similar in DPSCs seeded on both membranes.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-4 mRNA levels were also increased by CHI–HAp–collagen. BMP-4 is a member of the transforming growth factor superfamily that is important in tooth generation and formation, osteoblast differentiation, and matrix secretion [ 51 ]. On the other hand, the level of RUNX2 mRNA was similar in DPSCs seeded on both membranes.…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between TWIST1 and RUNX2 coordinates craniofacial muscle development (Han et al, 2021). Studies have shown that both the canonical and non-canonical SMAD-dependent signaling pathways control the proliferation and differentiation of dental MSCs as well as osteogenesis and skeletal development (Liu et al, 2022;Wu et al, 2016). Histone deacetylation via HDACs is an important function of the multiprotein epigenetic complexes that interact with many TFs, including RUNX2 and LEF1, during skeletal development (Jensen et al, 2010;Huynh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated crosstalk among the bone morphogenic protein (BMP), fibroblast growth factor (FGF) and WNT signaling pathways from the dental epithelium to the mesenchyme underlies the regulation of the odontogenic regulatory network during early tooth development (Chen et al, 2009). BMP signaling utilizes the canonical and non-canonical SMAD signaling pathways, which engage different TFs including RUNX2 and SP7 to initiate the differentiation of MSCs along the odontoblastic lineage (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…65,68,69 BMP-2 regulates the development of dental pulp stem cells (DSPC) into odontoblast-like cells and promotes the expression of tooth-associated genes. 70 In three dimensional pellet cultures, human recombinant BMP2 prompted the differentiation of pulp stem/ progenitor cells into odontoblasts. 39 Side population (SP) cells from dental pulp cells BMP-2 integrated were autologously transplanted on the amputated pulp and stimulated the production of reparative dentin.…”
Section: Growth Factors In Dentin Regenerationmentioning
confidence: 99%